2011
DOI: 10.1136/ard.2010.144725
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in obese people has structure-modifying effects on medial but not on lateral knee articular cartilage

Abstract: Background Obesity is an important risk factor for knee osteoarthritis (OA), Weight loss can reduce the symptoms of knee OA. No prospective studies assessing the impact of weight loss on knee cartilage structure and composition have been performed. Objectives To assess the impact of weight loss on knee cartilage thickness and composition. Methods 111 obese adults were recruited from either laparoscopic adjustable gastric banding or exercise and diet weight loss programmes from two tertiary centres. MRI was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
108
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 55 publications
11
108
2
1
Order By: Relevance
“…Previously, 1 study reported a preventive effect of weight loss on cartilage thickness of the knee (18). However, this was an observational study without validated clinical or radiologic OA outcomes, making the results less applicable in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, 1 study reported a preventive effect of weight loss on cartilage thickness of the knee (18). However, this was an observational study without validated clinical or radiologic OA outcomes, making the results less applicable in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In trials among subjects with and without established knee OA, weight loss was shown to have advantageous structure-modifying, systemic, and clinical effects (15)(16)(17)(18)(19)(20)(21). In a systematic review on the effects of weight loss on knee OA patients, a weight loss of at least 5% of body weight was indicated for symptomatic relief (22).…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that obesity increases the risk for progression in especially varus-aligned extremities (47). Previous studies have shown that the medial compartment in general is exposed to higher rates of cartilage loss in people with osteoarthritis, which could be attributed to a greater proportion of ground reaction forces by the medial tibiofemoral compartment even in normally aligned knees (40,48).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previously investigators reported that the percentage of weight loss is significantly associated with change in cartilage volume (19) and composition (40) of the medial tibia. However, in the previous studies, participants were followed up within a very inhomogeneous and shorter period of time, and the study cohorts with different degrees of weight loss, the group with a substantial amount of weight loss (.10% weight loss) showed significantly lower odds of cartilage degeneration when compared with the stable-weight reference group, whereas the odds were not significantly lower when we compared the 5%-10% weight loss group with the stable-weight group.…”
Section: Discussionmentioning
confidence: 99%
“…[6] On the other hand, the effect of weight loss in the structural progression of knee OA is still not established, and different studies have reached contrary conclusions. [7,8] A dose-response relationship between the extent of percentage change in body weight and improvement in joint symptoms has been demonstrated, with more robust effects with at least 10% reduction in body weight. [9] A reasonable time frame to achieve this goal is 6 months, with a weight reduction rate of 250-500 or 500-1000 g/week in persons with a BMI > 35 kg/m 2 .…”
Section: Effects Of Weight Loss In Oamentioning
confidence: 99%